Monte Carlo simulation and PMF model for assessing human health risks associated with heavy metals in groundwater: a case study of the Nubian aquifer, Siwa depression, Egypt - Eid, Mohamed Hamdy; Mikita, Viktoria; Eissa, Mustafa; Ramadan, Hatem Saad; Mohamed, Essam A.; Abukhadra, Mostafa R.; El-Sherbeeny, Ahmed M.; Bellucci, Stefano; Kovács, Attila; Szűcs, Péter (Frontiers in Earth Science, 2024)
IntroductionThe groundwater in arid countries such as Egypt represent the main water resources in the desert regions due to the long distance between these regions (oasis) and Nile River. Contamination of these limited water resources with toxic metals threaten the health of individuals in these regions.MethodsThe current study integrates isotopic tracers, hydrogeochemistry, geophysical logs, positive matrix factorization (PMF model), and Monte Carlo (MCS) simulation for pollution source apportionment and health risks associated with heavy metals in the Nubian Sandstone aquifer (NSSA).Results and DiscussionThe water resource used for drinking purposes (NSSA) is pale meteoric water (non-rechargeable aquifer). Silicate weathering, old trapped sea water, reverse ion exchange evaporation, and dissolution are the dominant mechanisms controlling water chemistry. PMF model showed that the major ions and heavy metals in groundwater of the NSSA originated from four significant sources (anthropogenic activities, dissolution of minerals, iron-bearing minerals, mixing with old trapped seawater, and hydrothermal water). The total risk (HI) oral values highlighted significant non-carcinogenic dangers for adults and children through the oral exposure. At the same time, dermal contact posed a no risk for adults and a high risk for children. Most samples had carcinogenic risk (CR) values higher than the allowed limits (1.0E-4) for metals like Cadmium, chromium, and lead, suggesting carcinogenic effects across all age groups. The Monte Carlo approach-based health concern evaluation model assessed the 5th % CR oral values (child) as 0.00012, 0.0036, and 0.0088 for Cd, Cr, and Pb, respectively, indicating more significant potential dangers to children. Urgent and comprehensive water treatment measures are imperative to mitigate the identified carcinogenic and non-carcinogenic health risks in the study area.